Effectiveness of Medication, Surgery, and Combination Therapy to Decrease Intraocular Pressure on Glaucoma Outpatient at Outpatient Ophthalmic Clinic Dr. Soetomo General Hospital Surabaya in January – December 2017 - Muhammad Bagas Pratista; Nurwasis Nurwasis; Kusuma Eko Purwantari; Indri Wahyuni (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Highlights:1. Combination of medication and surgery on glaucoma had the least post-therapy intraocular pressure.2. There was no significant difference in the efficacy of drugs, surgeries, and combination of both therapies for glaucoma intraocular pressure reduction. AbstractIntroduction: Glaucoma leads to blindness in its end stage. Quality of life drops as visual field loss as progressive optic nerve damage since high intraocular pressure elevation. Glaucoma treatment focused on aqueous humor regulation, thus the intraocular pressure is maintained at normal.Methods: This was a retrospective analytical study using secondary data gathered from medical records as total sampling data. The sample was determined by the purposive non-probability technique. The mean of intraocular pressure after therapies was defined as the dependent variable while the independent variable was the type of therapy.Results: Combined therapy (16.00 ± 6.77 mmHg) had the least post-therapy intraocular pressure. The statistical test indicated no significant difference in the effectiveness of medication, surgery, and combination therapy for glaucoma intraocular pressure reduction.Conclusion: There was no prominent difference in the efficacy of drugs, surgeries, and combined therapies for glaucoma intraocular pressure reduction.